DIFFERENCES IN LEVELS OF KNOWLEDGE AND BEHAVIOR OF COVID-19 PREVENTION BETWEEN MEDICAL PERSONNEL AT CUT NYAK DHIEN GENERAL HOSPITAL AND HARAPAN SEHAT HOSPITAL - Yennita; Imran; Mudatsir (CV. Radja Publika, 2023)
The role of health workers is the most important part in tackling the Covid-19 pandemic. All coping policies affect the services provided in hospitals so that they have a negative impact on the health care sector. To reduce the transmission rate, good knowledge and behavior is needed for health workers. The purpose of this research is to know the differencelevel of knowledge and behavior of Covid-19 prevention among medical staff at Cut Nyak Dhien Hospital and Harapan Sehat Hospital. The type of method in this research is quantitative. The data collection technique used a questionnaire with a total sampling technique and the number of samples was 128 people. The analysis used is the chi square test and Independent Sample T-Test. The results showed that there was a relationship between the level of knowledge and behavior of Covid-19 prevention at Cut Nyak dhien Hospital and Harapan Sehat Hospital with scoresP-value= 0.068 and 0.001 (p <0.05) while the Independent Sample T-Test showed that there was a significant difference between the knowledge of health workers at Cut NyakDhien Hospital and Harapan Sehat Hospital with a p valuevalue=( 0.039) < 0.05 while for prevention behavior the value isp-value=(0.009) <0.05 conclusion: There are differences in the level of knowledge and preventive behavior of medical personnel in the hospital.